Post pollination events in a self-sterile hexaploid monoembryonic lineage of Handroanthus serratifolius (Vahl) S. Grose (Bignoniaceae) - Alves,Mariana Ferreira (2019)
ABSTRACT In diploid late-acting self-incompatible (LSI) species of Bignoniaceae, self-pollinated pistils show a marked delay in ovule penetration by pollen tubes, followed by delayed, but otherwise normal, initial stages of endosperm development and subsequent pistil abscission. Most polyploid species of Bignoniaceae are apomictic and set selfed fruits with viable polyembryonic seeds carrying adventitious embryos. Handroanthus serratifolius is a polyploid species with sporophytic apomictic individuals that produce polyembryonic seeds after either self- or cross-pollination, and other LSI individuals that produce exclusively monoembryionic seeds. Our aim was to determine whether self-sterility events in the latter are similar to those observed in other diploid LSI species of Bignoniaceae. No conspicuous differences in the progress of ovule penetration, fertilization and early stages of endosperm development were observed between selfed and crossed pistils, which contrasts with the marked delay observed in these events after self-pollination in diploid LSI species of the family. Adventitious embryo precursor cells (AEPs) were observed in some ovules, but they apparently do not develop into embryos. We believe that the AEPs in these plants represent a ‘potential’ for sporophytic apomixis, which would explain the similar behaviour of post-pollination events in selfed vs. crossed pistils despite their inability to set fruits after selfing.